Empowerment of “Terasi Rebon” Seafood Processed Industry Craftsmen for the Development of Leading Potential for Highly Competitive Coastal Areas in Tuban, East Java - Mahmudah Enny W; Muslichah Erma Widiana; Abdul Fattah; Soehardjoepri Soehardjoepri (LPPM of NAROTAMA UNIVERSITY, 2022)
One of the superior products from processed sea fish in the famous Tuban coastal area is Terasi. Regional Superior Product Development Program (PPPUD) entitled Empowerment of Processed Sea Product Industry Craftsmen “Terasi Rebon” for the Development of Leading Potential for Highly Competitive Coastal Areas in Tuban, East Java. The problem with partners in terms of production in individual companies is the strengthening of production. So far, operational activities have not been carried out in a professional manner, still with a family system and there is no variety of flavors and packaging, so it is necessary to strengthen the operational management functions which include marketing, finance and tax management, information, human resources and production. For product development, partners need to innovate and be creative with flavor variants and packaging of rebon shrimp paste. Individual partner companies in marketing their products are done in a conventional way so that marketing is still limited around the East Java area. SOLUTIONS to this community service program are: Improving the quality, energy efficiency and processing time of rebon shrimp paste production through the design of the